Agriculture in print - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
All there is to know on locally printed material on agricultural issues for grassroot farmers in Ghana and Uganda, these useful results of very thorough research could serve to encourage similar studies for other countries.Locally generated printed...